1998
DOI: 10.1080/08990229870682
|View full text |Cite
|
Sign up to set email alerts
|

"Warmth-insensitive fields": evidence of sparse and irregular innervation of human skin by the warmth sense

Abstract: Although more acute in some areas of the body than in others, temperature sensitivity is assumed to be present throughout the skin. Only when very small stimuli have been used (e.g., approximately 1 mm2) has sensitivity to warming or cooling appeared discontinuous. Here we report the discovery of patches of skin several square centimeters in area within which heating cannot be detected until skin temperature exceeds the thresholds of C heat-sensitive nociceptors (>41 degrees C). These warmth-insensitive fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Green and Cruz (1998) found that small patches of healthy skin in which warmth sensitivity was absent had significantly higher heat pain thresholds than adjacent skin with normal warmth sensitivity. Similarly, Defrin et al (2001;2002) reported that in spinal cord injury patients, regions of the body where warmth sensitivity had been lost had abnormally high heat pain thresholds.…”
Section: Discussionmentioning
confidence: 97%
“…Green and Cruz (1998) found that small patches of healthy skin in which warmth sensitivity was absent had significantly higher heat pain thresholds than adjacent skin with normal warmth sensitivity. Similarly, Defrin et al (2001;2002) reported that in spinal cord injury patients, regions of the body where warmth sensitivity had been lost had abnormally high heat pain thresholds.…”
Section: Discussionmentioning
confidence: 97%
“…Ten subjects were dismissed after session 1 because they did not develop mechanical hyperalgesia after a 5 min, 46°C heating (see below, Induction and quantification of hyperalgesia). Four subjects were dismissed after session 1 because of too large areas on the volar forearm that were insensitive to warmth (tested by touching different spots on the forearm for 3 s with the thermode heated to 40°C) (Green and Cruz, 1998). Twenty-one subjects were dismissed after session 2 because of large dayto-day variability (Ͼ25% increase or decrease in pinprick hyperalgesic area).…”
Section: Methodsmentioning
confidence: 99%
“…During pretesting, a 41°C search stimulus was applied to the dorsum of the subject's foot to identify areas sensitive to innocuous heat. Six probe-sized (2.6 cm 2 ) warmth-sensitive areas were identified and used as guides for placement of the thermal stimuli to avoid warmth-insensitive regions during the experiment (10).…”
Section: Methodsmentioning
confidence: 99%